Experimental Characterization of a Functionally Graded Composite Using Recycled Steel Fiber - Mohamed Yagoub; Mekki Mellas; Adel Benchabane; Abdallah Zatar (Civil Engineering Journal, 2022)
Many industries have recently focused on cost-effective materials with good mechanical properties. Steel fiber reinforced cementitious composites have proven their mechanical performance in industrial and structural components. The concept of recycled fiber-reinforced FGM is used as an alternative construction material, which can be one of the proposed cost-effective solutions. To achieve these objectives, an experimental program has been developed. A cementitious composite based on local materials was strengthened in two designs; one strengthened over the entire cross-section and the other strengthened only in the tensile zone. We also substituted a functional gradient material reinforced with recycled fibers considering the following volume fractions: 0, 0.5, 1, and 1.5%. This paper investigates the feasibility of using recycled fibers from industrial waste from steel wool manufacturing as reinforcement. We also characterized their mechanical properties using ultrasonic pulse velocity, compressive strength, flexural tensile strength, and shear strength. The results show that the corrugated recycled fibers are the ideal choice to increase the mechanical performance of the reinforced composite, including the improvement of flexural and shear behaviors. Therefore, the investigated FGC could be a valuable tool to optimize the design process in various structural applications and make the production of mechanically and environmentally economical composites possible. Doi: 10.28991/CEJ-2022-08-05-03 Full Text: PDF